Reason and revelation: Kant and the problem of authority - Enns, Phil (International journal for philosophy of religion, 2007)
This paper explores the significance of authority for Kant’s understanding of the relationship between reason and revelation. Beginning with the separation of the faculties of Theology and Philosophy in Conflict, it will be shown that Kant sees a clear distinction between the authority of reason and that of revelation. However, when one turns to Religion, it is also clear that Kant sees an important, perhaps necessary, relationship between the two. Drawing on a variety of texts, in particular those concerning the public and private use of reason, this paper then explores the relationship between the authority of reason and that of revelation. From this discussion, several conclusions will be drawn regarding Kant’s understanding of the relationship between reason and revelation, namely that while distinct, the two are not necessarily in conflict and that, ultimately, the proper functioning of public reason must include some reference to revelation.